KEMAMPUAN REPRESENTASI MATEMATIS PADA SISWA INDONESIA BERDASARKAN KARAKTERISTIK CARA BERPIKIR: SISTEMATIK LITERATUR REVIEW - Inayah, Clara fadhilah; Dasari, Dadan (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2023)
The purpose of this study is to describe the results of mathematical representation ability based on the characteristics of ways of thinking. The method used in this research is a Systematic Literature Review (SLR). The data in this study amounted to 9 publications related to mathematical representation ability based on the characteristics of ways of thinking. The publication data are publications indexed by SINTA or Google Scholar, published in the range of 2018-2023, and located in Indonesia. The description in this study was reviewed based on the year of publication, journal index, publication media, methods used, education level of the research subject, research location, and research results. Through SLR, it was obtained that the most publications on mathematical representation ability based on the characteristics of ways of thinking occurred in 2019, repositories and Google Scholar became the publication media that published the most research, and qualitative methods became the most dominating method in this study, junior high school students became the most research subjects used as samples in this study, and the island of Java became the most dominant research location in Indonesia related to this research. In addition, it can be concluded that each student is unique in their thinking characteristics. keyword: Mathematical Representation Ability, The Characteristics of Ways of Thinking, SLR